1987
DOI: 10.1126/science.236.4800.403
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis: New Perspectives from Surface Science

Abstract: One-sixth of the value of all goods manufactured in the United States involves catalytic processes. However, in spite of this dramatic economic impact, little is known about this broad subject at the molecular level. In the last two decades a variety of techniques have been developed for studying at the atomic level the structure, composition, and chemical bonding at surfaces. These techniques have been used to study adsorption and reaction on metal single crystals in an ultrahigh vacuum environment or to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…Studies have shown that certain bimetallic catalysts have both higher activity and better product selectivity than their monometallic counterparts [18][19][20][21], and mixedmetal cluster complexes are found to be good precursors for the preparation of supported bimetallic nanoparticles [22][23][24][25]. Cluster complexes of platinumruthenium immobilized on mesoporous silica have been shown to exhibit high activity for catalytic hydrogenation reactions [18,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that certain bimetallic catalysts have both higher activity and better product selectivity than their monometallic counterparts [18][19][20][21], and mixedmetal cluster complexes are found to be good precursors for the preparation of supported bimetallic nanoparticles [22][23][24][25]. Cluster complexes of platinumruthenium immobilized on mesoporous silica have been shown to exhibit high activity for catalytic hydrogenation reactions [18,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The presence of differing transition metals may offer molecular approaches to the design of catalysts with high activity and selectivity, because the intrinsic polarity of heterometallic bonds may afford enhanced activation and direct the selectivity of substrate-cluster interactions. [4,5] Mixed-metal clusters can possess readily tailored physical properties (such as optical limiting) because of facile structural manipulation resulting from incorporation of differing metal atoms and the variation of the metal core skeletons, [6] so they continue to command attention.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed-metal cluster complexes have been shown to be good precursors for the preparation of supported bimetallic nanoparticles . It has been shown that certain bimetallic catalysts have both higher activity and better product selectivity than their monometallic counterparts . Supported platinum–ruthenium clusters have been shown to exhibit high activity for catalytic hydrogenation reactions when immobilized on mesoporous silica. , The use of NHCs in metal cluster chemistry is still relatively limited.…”
Section: Introductionmentioning
confidence: 99%